PRODUCTIVITY OF CHICORY ROOT SEEDS DEPENDING ON THE PLACING PLANTS METHOD - Bakhmat , M. I.; Tkach , O. V.; Stepanchenko , V.M. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Experimental studies have established the features of the formation of a productive stem stand, productivity and grain quality of domestic varieties of spring triticale when grown on two backgrounds of nutrition. Providing crops of spring triticale with elements of mineral nutrition is a necessary condition for increasing the grain productivity of new varieties when grown in the Steppe zone. The highest yields of 3.77 and 3.48 t/ha of spring triticale against a natural background were formed by the Khlebodar Kharkovsky and Boriviter varieties, against the background of N30P30K30 - 4.72 t/ha, 4.58 t/ha and 4.57 t/ha of the Khlebodar variety Kharkovsky, Legin and Solntsedar Kharkovsky. The yield of triticale depended on the conditions of moisture during the formation of vegetative organs and the laying of elements of individual plant productivity, and the share of the influence of the nutritional background was 57.2–78.0%, varietal characteristics - 7.8–21.1%. The content of protein and gluten in triticale grain depended both on weather conditions and varietal characteristics. In triticale, the content of protein and gluten was 9.7–11.8% and 14.2–17.1% (without fertilizers), N30P30K30 was 10.4–12.2% and 14.9–17.3%, respectively. The higher content of protein on both backgrounds of nutrition was provided by the Volya variety, and gluten - by Dar Khleba